Sex differences in brain mitochondrial metabolism: influence of endogenous steroids and stroke. (18th February 2018) - Gaignard, P.; Fréchou, M.; Liere, P.; Thérond, P.; Schumacher, M.; Slama, A.; Guennoun, R.
Abstract : Steroids are neuroprotective and a growing body of evidence indicates that mitochondria are a potential target of their effects. The mitochondria are the site of cellular energy synthesis, regulate oxidative stress and play a key role in cell death after brain injury and neurodegenerative diseases. After providing a summary of the literature on the general functions of mitochondria and the effects of sex steroid administrations on mitochondrial metabolism, we summarise and discuss our recent findings concerning sex differences in brain mitochondrial function under physiological and pathological conditions. To analyse the influence of endogenous sex steroids, the oxidative phosphorylation system, mitochondrial oxidative stress and brain steroid levels were compared between male and female mice, either intact or gonadectomised. The results obtained show that females have higher a mitochondrial respiration and lower oxidative stress compared to males and also that these differences were suppressed by ovariectomy but not orchidectomy. We have also shown that the decrease in brain mitochondrial respiration induced by ischaemia/reperfusion is different according to sex. In both sexes, treatment with progesterone reduced the ischaemia/reperfusion‐induced mitochondrial alterations. Our findings indicate sex differences in brain mitochondrial function under physiological conditions, as well as after stroke, and identify mitochondria as a target of the neuroprotective properties of progesterone. Thus, it is necessary to investigate sex specificity in brain physiopathological mechanisms, especially when mitochondria impairment is involved.